2010
DOI: 10.1111/j.1399-3046.2009.01258.x
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of post-transplant lymphoproliferative disease in the era of molecular EBV monitoring

Abstract: Pediatric PTLD is often associated with primary EBV infection and immunosuppression. The aim was to retrospectively review the spectrum of histologically documented PTLD for two time intervals differentiated by changes in use of molecular EBV monitoring. Eleven of 146 patients (7.5%) in 2001-2005 (Era A) and 10 of 92 (10.9%) in 1993-1997 (Era B) were diagnosed with PTLD. The median age at liver transplantation (0.8 and 0.9 yr, respectively) and the median duration between liver transplant and diagnosis of PTLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…A total of 21 international published studies [13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were found that met our criteria. Table 1 summarizes data of the enrolled studies.…”
Section: Study Populationmentioning
confidence: 99%
“…A total of 21 international published studies [13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were found that met our criteria. Table 1 summarizes data of the enrolled studies.…”
Section: Study Populationmentioning
confidence: 99%
“…In the latter period, patients had less advanced histological disease at presentation and no deaths, compared to advanced disease and 3 deaths in the earlier era. The difference was ascribed to implementation of molecular EBV monitoring and preemptive reduction in immunosuppression [7]. …”
Section: Diagnosis Of Ptldmentioning
confidence: 99%
“…In liver transplant recipients, PTLD is reported in up to 2.8% of adults and up to 15% of children [3]. Mortality has been reported as high as 50%, although current management strategies appear to result in improved outcomes [47]. Here we will review the pathophysiology, risk factors, clinical presentation, and management of PTLD after liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Preemptive IS alleviation (tacrolimus tapering, corticoids arrest) induced lowering of viral load in all and led to rejection in 1/11 patient. Another retrospective comparison of children after liver transplantation with or without EBV load monitoring (2001-2005 and 1993-1997), with preemptive IS tapering in case of high viral load, showed no difference in PTLD incidence (7.5 and 10.9 %, respectively) (Kerkar et al 2010). PTLD occurring in the 2001-2005 era were, however, less advanced (polymorphic versus monomorphic, p = 0.03), with no mortality as compared to 3/10 deaths before.…”
Section: Risk Factors and Preventionmentioning
confidence: 91%